Regions, globalization, and the knowledge-based economy - Dunning, John H. (Oxford : Oxford University Press, 2000)
The theme of this volume is the impact of the increasing globalization of economic activity, and the advent of the knowledge-based economy, on he spatial distribution of economic activity, both between countries and within countries.
Includes bibliographical references and index.
osc 02/09/2016
Loans
Keywords: Globalization; Knowledge management; Regional economics; International business enterprises